Understanding Chaos Theory’s Implications on Strategic Decision-Making - Rene Paquibut, Nuha Hamada, (Opción, 1970)
Strategic management is the process of establishing long term goals, deciding what strategies are appropriate to achieve those goals, and carrying out the needed steps to implement those strategies. The effectiveness of the strategy lies in the precision of the analysis given that an organization is a complex system. One theory that has gained attention in strategic management is the chaos theory, which is the study of nonlinear dynamic systems like business organizations. This paper explored related literature to understand the general application of the theory in the process of decision-making. The paper illustrates that the theory can be considered as a critical framework in the process of decision-making in organizations